Levodopa-refractory hyperprolactinemia and pituitary findings in inherited disorders of biogenic amine metabolism - Yıldız, Yılmaz; Kuseyri Hübschmann, Oya; Akgöz Karaosmanoğlu, Ayça; Manti, Filippo; Karaca, Meryem; Schwartz, Ida Vanessa; Pons, Roser; López-Laso, Eduardo; Palacios, Natalia Alexandra Julia; Porta, Francesco; Kavecan, Ivana; Balcı, Mehmet Cihan; et al. (Journal of inherited metabolic disease, 2023)
Elevated serum prolactin concentrations occur in inherited disorders of biogenic amine metabolism because dopamine deficiency leads to insufficient inhibition of prolactin secretion. This work from the International Working Group on Neurotransmitter Related Disorders (iNTD) presents the results of the first standardized study on levodopa-refractory hyperprolactinemia (LRHP; >1000 mU/L) and pituitary magnetic resonance imaging (MRI) abnormalities in patients with inherited disorders of biogenic amine metabolism. Twenty-six individuals had LRHP or abnormal pituitary findings on MRI. Tetrahydrobiopterin deficiencies were the most common diagnoses (n = 22). The median age at diagnosis of LRHP was 16 years (range: 2.5-30, 1st-3rd quartiles: 12.25-17 years). Twelve individuals (nine females) had symptoms attributed to hyperprolactinemia: menstruation-related abnormalities (n = 7), pubertal delay or arrest (n = 5), galactorrhea (n = 3), and decreased sexual functions (n = 2). MRI of the pituitary gland was obtained in 21 individuals; six had heterogeneity/hyperplasia of the gland, five had adenoma, and 10 had normal findings. Eleven individuals were treated with the dopamine agonist cabergoline, ameliorating the hyperprolactinemia-related symptoms in all those assessed. Routine monitoring of these symptoms together with prolactin concentrations, especially after the first decade of life, should be taken into consideration during follow-up evaluations. The potential of slow-release levodopa formulations and low-dose dopamine agonists as part of first-line therapy in the prevention and treatment of hyperprolactinemia should be investigated further in animal studies and human trials. This work adds hyperprolactinemia-related findings to the current knowledge of the phenotypic spectrum of inherited disorders of biogenic amine metabolism.